2021
DOI: 10.1016/j.drugpo.2020.102833
|View full text |Cite
|
Sign up to set email alerts
|

Supplying synthetic opioids during a pandemic: An early look at North America

Abstract: International commerce and travel have been restricted in order to limit the spread of COVID-19. The illegal trafficking in drugs, which is often concealed in other commercial activity, will be affected by these disruptions. This is particularly true for precursor chemicals, controlled substances of synthetic origin, and new psychoactive substances coming from Asia. China hosts large and under-regulated pharmaceutical and chemical sectors that provide many of the active ingredients used both in legitimate medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Socioeconomic instability due to decreased income generation opportunities, and shifting drug markets due to changes in global drug trafficking [ 14 ], may also exacerbate vulnerability among PWUD, both indirectly, by affecting drug use patterns, and directly, through increased risk of overdose from contaminated or increasingly potent supplies [ 37 39 ]. Preventing harms, both in the immediate wake of Big Events and in the longer term, requires continued operation and funding of harm reduction services and monitoring of the drug supply, including through scale-up of drug checking services [ 40 ], which were accessed by a limited number in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic instability due to decreased income generation opportunities, and shifting drug markets due to changes in global drug trafficking [ 14 ], may also exacerbate vulnerability among PWUD, both indirectly, by affecting drug use patterns, and directly, through increased risk of overdose from contaminated or increasingly potent supplies [ 37 39 ]. Preventing harms, both in the immediate wake of Big Events and in the longer term, requires continued operation and funding of harm reduction services and monitoring of the drug supply, including through scale-up of drug checking services [ 40 ], which were accessed by a limited number in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…While the impact of big events on PWUD is well documented, less is known about the effects of big events on drug markets. Some have speculated since legal and illegal markets might be linked, it was conceivable that the global slowdown in commercial activity and transportation, which are central to drug markets, could disrupt the circulation of chemical precursors required to produce fentanyl and fentanyl analogs, thereby affecting the drug supply [8]. This assessment seems to be confirmed by a study of PWUD in Georgia that showed that the perceived availability of drugs was reduced during the COVID-19 lockdown, with participants switching to alternative substances if their drug of choice was not available [9].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] In addition, border closures, supply chain disruptions and increased pricing have altered the availability and toxicity of the illegal drug supply. 13,[19][20][21][22] As the pandemic continues to evolve and impose changes to human behaviour, as well as access to support programs and services, the injury epidemiology and substance use patterns in Canada may also change. 23,24 Studies conducted during the pandemic have shown an increase in substance-related hospital discharges, as well as overall changes in the injury landscape during the pandemic.…”
mentioning
confidence: 99%